Association of early surgery and mortality in patients with native or prosthetic valve endocarditis. (3rd May 2023) - Tao, M; Manikantan, P; Despotidis, G; Alkhalil, A; Parikh, P; Pyo, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Infective endocarditis (IE) is a disease associated with high risk of morbidity and mortality. Recent studies suggests that surgery during index hospitalization may be performed without increased risk of mortality. However, differences in this association in patients with native valve IE and prosthetic valve IE remain unclear. Purpose: The purpose of this meta-analysis is to explore differences in the association between early surgery and mortality in patients with native valve IE and prosthetic valve IE. Methods: We performed a literature search for studies reporting an association between early surgery and study endpoints in patients with either native valve IE or prosthetic valve IE. The primary endpoint was in-hospital mortality. The secondary endpoints was long-term mortality. The search included the following databases: Ovid MEDLINE, EMBASE, Web of Science, and Google Scholar. The search was not restricted to time or publication status. Studies reporting mixed native and prosthetic valve populations were excluded. Results: A total of 10 studies with 5493 participants (2505 with early surgery vs 2988 with conventional therapy) were included. The mean duration of follow-up was 55 months (ranging between 12 to 120 months). Early surgery in patients with native valve IE was associated with lower risk of in-hospital mortality (OR 0.48, 95% CI 0.28, 0.83; p<0.01). Early surgery in patients with native valve IE was associated with lower risk of long-term mortality, however this effect was primarily driven by a single study (OR 0.26, 95% CI 0.08, 0.83; p=0.02). Early surgery in patients with prosthetic valve IE was not significantly associated with risk of in-hospital mortality, however there is a trend toward lower risk (OR 0.77, 95% CI 0.58, 1.02; p=0.07). There was not enough studies reporting long-term outcomes to assess the association between early surgery and long-term mortality in patients with prosthetic valve IE Conclusions: Early surgery is associated with lower risk of in-hospital mortality in patients with native valve IE and is not associated with increased risk of mortality in patients with prosthetic valve IE. Further high-quality studies are needed to elucidate the association between early surgery and long-term outcomes in both patients with native valve IE and prosthetic valve IE.